Effect of in ovo Injection of Selenium in Isa Brown Fertile Eggs on Hatching Process, Chicks Quality and Post Hatch Growth - kwassi, Tona; Wéré, Pitala; Djeuta, Ngueda (ANSINET, 2021)
Background and Objective: Selenium is an essential micro-nutrient for the maintenance of animal and human health. It is well known for its anti-oxidant activities. The aim of the present study was to evaluate the effects of in ovo Selenium administration in Isa Brown fertile eggs on the hatching process and post hatch growth. Materials and Methods: A total of 750 hatching eggs from 40 weeks old Isa Brown breeders were set and at day 18th of incubation, 600 eggs with live embryos were assigned to 5 treatments of 120 eggs each. These groups were: (T0–) eggs without in ovo injection (negative control); (T0+) eggs injected with NaCl 9‰ (positive control); (T10) eggs injected with 10 μg Selenium per egg; (T20) eggs injected with 20 μg Selenium per egg and (T30) eggs injected with 30μg Selenium per egg. Parameters such as pipping time, hatching rate, chick’s quality, blood biochemistry parameters, organs and chicks weight were assessed at hatch. During the rearing period, weight of chickens was recorded weekly. Results: Results showed that T0– had significantly (p<0.05) the shortest hatching duration compared to others. No significant (p<0.05) difference was observed for hatchability rate. However, chicks from T30 had significantly (p<0.05) higher quality and growth after hatch. Chick’s quality was higher as the Selenium concentration increased in the injected solution. Conclusion: In conclusion, the injection of Selenium in the fertile eggs improved the growth performance of chicks.
International Journal of Poultry Science
Keywords: In ovo nutrition; Isa brown breeders; Hatching eggs; Hatching process; Hatchability; Chick's quality; Growth performance; Sergers Ludo; Fafiolu Adeboye; University of Lome; Togo; CERSA